Role of insertion layer controlling wavelength in InGaAs quantum dots - Park, SK; Park, YJ; Kim, EK; Park, CJ; Cho, HY; Lim, YS; Lee, JY; Lee, C (JAPAN SOC APPLIED PHYSICS, 2002)
We have observed the red shift of the emission wavelength in InGaAs/GaAs quantum dots by employing a very thin AlGaAs insertion layer (IL). The thin AlGaAs layer of less than 10 nm in thickness,vas inserted immediately after the formation of self-assembled InGaAs quantum dots (QDs) on a GaAs buffer layer. The low, temperature ( 15 K) photoluminescence peak typically appears at around 1.1 mum in the sample without IL whereas it is red-shifted up to 1.25 mum a the 11, thickness increases. It is interpreted that the thin AlGaAs IL releases the local strain around QDs asymmetrically.
Keywords: TEMPERATURE; OPERATION; GAINNAS